Mapping chromosome band 11q23 in human acute leukemia with biotinylated probes: identification of 11q23 translocation breakpoints with a yeast artificial chromosome. - Rowley, J D (1990)
Translocations involving chromosome 11, band q23, are frequent recurring abnormalities in human acute lymphoblastic and acute myeloid leukemia. We used 19 biotin-labeled probes derived from genes and anonymous cosmids for hybridization to metaphase chromosomes from leukemia cells that contained four translocations involving band 11q23: t(4;11)(q21;q23), t(6;11)(q27;q23), t(9;11)(p22;q23), and t(11;19)(q23;p13). The location of the cosmid probes relative to the breakpoint in 11q23 was the same in all translocations. Of the cosmid clones containing known genes, CD3D was proximal and PBGD, THY1, SRPR, and ETS1 were distal to the breakpoint on 11q23. Hybridization of genomic DNA from a yeast clone containing yeast artificial chromosomes (YACs), that carry 320 kilobases (kb) of human DNA including CD3D and CD3G genes, showed that the YACs were split in all four translocations. These results indicate that the breakpoint at 11q23 in each of these translocations occurs within the 320 kb encompassed by these YACs; whether the breakpoint within the YACs is precisely the same in the different translocations is presently unknown.